Evaluation of Communication Activities In Branding Success Jateng Gayeng - Ahmad Jailani Siregar; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Jateng Gayeng is one of the provincial tagline in Indonesia, Central Java which has a message of attraction, such as culture and art that characterize Central Java. Jateng Gayeng published through the media. Gayeng Jateng has now become the branding of Central Java. The reality of Central Java has not been too known by the community. It requires the Central Java government to develop all sectors in a conceptual manner based on the strength and potential of Central Java. Central Java through Central Java Gayeng is a branding that has the vision and mission to raise the image of Central Java to the national and international scene. Nevertheless, the era of globalization requires Central Java to be open to many things. Central Java nowadays has transformed into a modern province with the establishment of infrastructure and facilities in Central Java, but still refers to the existing culture. The description has become the rationale of this research that will focus on branding Gayeng Central Gayeng brand that must be created is a province that is identical with the strength of local culture. This study aims to describe the communication activities of Central Java government in branding Jateng Gayeng. This research uses mix method approach and analyzed with Models of Public Relation J.Grunig that is press agentry model, public information model, two way asymmetrical model, two way symmetrical model and branding concept from Kaparder prism with phsysic indicator, personality, culture, relationship, Reflection, and self image. This research shows that branding of Central Java Gayeng is done through several activities that have been designed by the related office by using communication activities. By holding various communication activities, it will increase the attraction of the people to visit Central Java. In the implementation of branding can not only rely on local government but there must be supporters such as local communities, investors and stakeholders. The success of branding in Central Java is measured by the number of tourist arrivals and the level of investment.